INTELLIGENCE AS A PRODUCT MARKETING STRATEGY IN THE INTERNATIONAL MARKET - Mohammad Noor Khairullah (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
One principal use of language is to communicate meaning, but it is also to establish and maintain relationship. There are the different aims in speaking skill and the implementation in activity, for casual conversation and discussion. The aim of this study is to know the influence of Intelligence in using English with the marketing strategy of a product in the International Market. The design of this study is correlation design since it used statistical measurement for the data analysis to describe the relationship between two variables and is analyzed by using Pearson-Product Moment formula. There are 62 purposive sampling from 4 classes and using three instruments: test of IQ, documentation, and assessment. The result of this study is the influence of Intelligence in using English and the marketing strategy of a product in the International Market is dominant with coefficient correlation 0.220. So, the null hypothesis (Ho) is rejected and the alternative hypothesis (Hi) is accepted.